An efficient technique for simultaneous local and overall buckling analysis of stiffened panels. (May 2019) - Deng, Jian; Wang, Xinwei; Yuan, Zhangxian; Zhou, Guangming
Highlights: An efficient technique is presented for buckling analysis of stiffened panels. A weak form quadrature plate element with stiffeners is formulated. Stiffener can be located anywhere in the plate other than along a nodal line of the plate element. Simultaneous local and overall buckling is performed by the presented technique. Abstract: The overall buckling and local buckling of stiffened panels are two possible failure modes and thus should be concerned by engineers in the preliminary design of lightweight structures. In this paper, an efficient technique is proposed to solve the local and overall buckling problem of stiffened panels simultaneously. A weak form quadrature plate element with stiffeners located anywhere in the plates other than along the nodal lines of the plate element is formulated. Explicit formulations with an arbitrary number of nodes are given. Improvement of solution accuracy can be easily done by increasing the number of element nodes if necessary. A convergence study is performed. Several numerical examples are given. Results are compared with either existing analytic solutions or finite element data for verification. It is shown that high accuracy can be achieved with a small number of nodes. In addition, the proposed method can allow a quick analysis of simultaneous overall and local buckling behavior of stiffened panels and thus may be suitable for optimization routines in preliminary design of stiffened panels.